2017
DOI: 10.3390/su10010031
|View full text |Cite
|
Sign up to set email alerts
|

Investigating How the Rents of Small Urban Houses are Determined: Using Spatial Hedonic Modeling for Urban Residential Housing in Seoul

Abstract: Abstract:The Seoul metropolitan government has launched the Urban Residential Housing (URH) program to address the shortage of small urban houses, and enhance residential stability for the increasing number of one-and two-person households in Seoul, Korea. While studies have examined the price premium of locational and neighborhood environmental features for houses in general, little is known about how and to what extent these features influence the rents of small urban houses. We estimate and compare conventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…Neighborhood environment is also a significant attribute for houses. In addition, residents prefer to live proximate to open spaces [17,18], commercial centers [38], primary and middle schools [39], and universities [40]. Building structure, which refers to the internal attributes of a house's structure, also play an important role in housing utility value.…”
Section: Selection Of Explanatory Variablesmentioning
confidence: 99%
“…Neighborhood environment is also a significant attribute for houses. In addition, residents prefer to live proximate to open spaces [17,18], commercial centers [38], primary and middle schools [39], and universities [40]. Building structure, which refers to the internal attributes of a house's structure, also play an important role in housing utility value.…”
Section: Selection Of Explanatory Variablesmentioning
confidence: 99%
“…Won and Lee [15] paid attention to how the rents of the URHs were determined in Seoul using the spatial hedonic price model. They reported that factors such as net residential area and accessibilities to subway and public facilities exerted positive impacts on rents [32].…”
Section: Review Of Relevant Studiesmentioning
confidence: 99%
“…A number of studies have analyzed the characteristics and the effects of the small houses on their neighborhoods, or investigated the pricing mechanism and affordability and suggested policy implications [3,[6][7][8][9][10][11][12][13][14][15][16]. Also, earlier studies have focused on analyzing the residential characteristics and the residential satisfaction factors of single and two-person households as the primary consumers of small urban residences [13,[17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…The externalities and spillover effect in housing markets have attracted growing scholarly interest [1][2][3][4][5][6][7]. Extensive studies have been reported for the housing markets in the developed world [8][9][10][11], while developing countries have also begun to pay attention [7,[12][13][14][15]. Meen [16] provides convincing economic explanations for the driving forces of spillover and summarizes four major mechanisms by which the housing price spillover can occur: migration, equity transfer, spatial arbitrage, and spatial patterns.…”
Section: Introductionmentioning
confidence: 99%